Isolation and Partial Characterization of a Bacteriocin Produced by a Newly Isolated Bacillus megaterium 19 Strain - Khalil, Rowaida; Elbahloul, Yasser; Djadouni, Fatima; Omar, Sanaa (Pakistan Journal of Nutrition, 2009)
A Bacillus megaterium 19 strain isolated from a mixture of fermented vegetable wastes, produced a bacteriocin that displayed a wide spectrum antimicrobial activity against food-spoilage microorganisms and possessed a bactericidal mode of action. The bacteriocin activity against Salmonella typhimurium and Staphylococcus aureus attained its maximum value during the mid stationary phase. Maximal bacteriocin activity (93% growth reduction) was achieved using MRS broth, at initial pH of 5.5-6.5 and at 30°C incubation temperature. High levels of bacteriocin activity (up to 85% growth reduction) were detected under limited or reduced oxygen levels. The inhibitory activity increased in mMRS broth with 4% sucrose and (0.10%) beef extract. The bacteriocin was thermally stable over a wide temperature range up to 100°C for 15 min and retained its activity at acidic and neutral pH values, but not at alkaline pHs. Full bacteriocin activity was expressed after 30 days of storage at 4°C, for 15 min of exposure to UV light. The bacteriocin was amylase and lipase sensitive, however, treatment with proteolytic enzymes resulted in a remarkable stability. SDS-PAGE analysis of the partially purified bacteriocin revealed an apparent molecular weight ranging from 3.496 to 6.512 kDa. The strain may have a potential use as food biopreservative, because of its promising thermostable technological properties and broad antimicrobial spectrum.